Exploring Principal Supervision in Enhancing Teachers’ Self-Renewal Capacity - Noviah Dwi Putranti Putranti; Aunurrahman; Afandi; Tomo Djudin; Halida (Jurnal Pendidikan Edutama, 2026)
This study aimed to describe the implementation of principal supervision in improving teacher self-renewal capacity at SMA Negeri 3 Pontianak. The study employed a descriptive qualitative method, with data collected through conversations, observations, and document analysis involving the principal and teachers. The results showed that the supervision positively contributed to enhancing teacher motivation, creativity, and professionalism through continuous guidance, feedback, and training. Supporting factors included the principal’s commitment and facility support, while obstacles involved limited time and teacher motivation. In conclusion, principal supervision effectively improves teacher self-renewal capacity, which positively impacts the quality of learning and education.